An animal model of nonconvulsive status epilepticus: a contribution to clinical controversies - Krsek, P; Mikulecká, A; Druga, R; Hlinák, Z; Kubová, H; Mares, P (Epilepsia, 2001)
PURPOSE: To characterize electroencephalographic and behavioral effects as well as electrophysiologic and morphologic consequences of a subconvulsive dose of pilocarpine in lithium chloride-pretreated rats. METHODS: Pilocarpine (15 mg/kg) was administered intraperitoneally to adult rats pretreated with lithium chloride (3 mEq/kg, i.p.). Behavior was observed for 2 h and videotaped in three consecutive sessions. At the same time, EEG was recorded from the sensorimotor cortex and the dorsal hippocampus. Threshold intensities of currents necessary to elicit hippocampal afterdischarges were determined 24 h and 1 week after the pilocarpine administration. The brains were histologically examined 1 week after pilocarpine administration using Nissl stain. RESULTS: Pilocarpine induced time-limited nonconvulsive status epilepticus (NCSE). Epileptic EEG activity concurrent with prominent behavioral features was observed both in the neocortex and, predominantly, in the hippocampus. No changes in afterdischarge thresholds were observed in the dorsal hippocampus 24 h and 1 week after NCSE. One week after NCSE, seizure-related brain damage was found mainly in the motor neocortical fields. CONCLUSIONS: Pilocarpine-induced NCSE in rats strongly resembles a short-term human complex partial status epilepticus. Our animal model is suitable for studying the possible adverse effects of prolonged nonconvulsive seizures.
Keywords: Behavior, Animal; Rats; Electroencephalography; pohybová aktivita; Pilocarpine; Neocortex; chlorid lithný; hipokampus; Disease Models, Animal; Rats, Wistar; mužské pohlaví; elektroencefalografie; pilokarpin; krysa rodu Rattus; Lithium Chloride; Status Epilepticus; modely nemocí na zvířatech; zvířata; Humans; Videotape Recording; status epilepticus; chování zvířat; neokortex; potkani Wistar; Motor Activity; videozáznam; lidé; Male; Hippocampus; Animals